2013
DOI: 10.1007/s10967-013-2860-9
|View full text |Cite
|
Sign up to set email alerts
|

Natural radionuclides in Italian diet and their annual intake

Abstract: This study was dedicated to the evaluation of the background activity concentration of natural radionuclides as 228Ra and 228Th of 232Th family, 226Ra of 238U family and 40K in the Italian daily diet. These radionuclides were determined by gamma spectrometry. 40K activity concentration, in the samples taken into account in the present paper, ranged between 70.5 (milk) and 181.1 Bqkg-1ww (pasta), 226Ra activity concentration ranged between 1.1 (milk) and 5.7 Bqkg-1ww (pasta), 228Ra and 228Th activity concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The standard International Atomic Energy Agency (IAEA) sources were used for calibration (IAEA, 2003: [6]). From the counting spectra, the activity concentrations of 226 Ra, 232 Th and 40 K was determined using computer program.…”
Section: Validation Of the Analytical Techniquementioning
confidence: 99%
“…The standard International Atomic Energy Agency (IAEA) sources were used for calibration (IAEA, 2003: [6]). From the counting spectra, the activity concentrations of 226 Ra, 232 Th and 40 K was determined using computer program.…”
Section: Validation Of the Analytical Techniquementioning
confidence: 99%
“…This matter has become a great concern as has been reported by many researchers in different part of the world. From eleven different countries, 58 types of vegetables have been studied with seven common types namely spinach, carrot, cucumber, tomato, pumpkin, green bean and potato [6][7][8][9][10][11][12][13][14][15][16]. However in Malaysia, only 16 types of vegetables have been studied with spinach and cucumber as the common type [17,18].…”
Section: -2506mentioning
confidence: 99%
“…However in Malaysia, only 16 types of vegetables have been studied with spinach and cucumber as the common type [17,18]. Studies conducted in ten different countries reported that 26 types of fruits have been studied with eight common types namely apple, pear, orange, mango, banana, papaya, grapes and watermelon [6][7][8][9][10][11][12][13][14][15][16]. Whereas in Malaysia, only nine types of fruits have been studied i.e.…”
Section: -2506mentioning
confidence: 99%
“…Whereas for category \1 and 12-17 years, the largest contributor is 226 Ra (44 and 53 % respectively) followed by 40 K and 232 Th. The large number of 40 K is not surprising as it is an essential element and being homeostatically controlled in the human body [2,30]. But different case happens with 226 Ra, where it can be absorbed into the blood stream and distributed to soft tissue and bones [31].…”
Section: Sample Analysismentioning
confidence: 99%
“…These radionuclides can enter the human body primarily by ingestion of food and drink [2]. One of the important food for human nutrition that contains all the macronutrients is milk [3].…”
Section: Introductionmentioning
confidence: 99%